1953
DOI: 10.1021/jf60014a003
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Insecticides, Development of Organic Phosphates as Systemic Insecticides

Abstract: Historical Review of the Work of Gerhard Schrader SYSTEMICS SYMPOSIUM G ERTAIN DERIVATIVES OF /3-FLUOROETHYL alcohol were found by Gerhard Schrader, of Farbenfabriken Bayer, in Germany, about 1935, to have strong insecticidal action (7, 3, 8). Outstanding compounds are shown in Table I.Compounds A and B, because of their high volatility, were limited in their application as agricultural pesticides.Schrader then prepared condensation products of aldehydes with /3-fluoroethyl alcohol and its derivatives (C and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1967
1967
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Early studies with organophosphate insecticides (Geary, 1953) indicated the importance of moderate lipophilicity (i.e. some water solubility) for systemic effect.…”
Section: Phloem Toxicologymentioning
confidence: 99%
“…Early studies with organophosphate insecticides (Geary, 1953) indicated the importance of moderate lipophilicity (i.e. some water solubility) for systemic effect.…”
Section: Phloem Toxicologymentioning
confidence: 99%
“…However, it must be recognized that most of them are ineffective against chewing insects and some compounds even exhibit a high mammalian toxicity. Since the first review on systemic insecticides by GEARY (1953), various aspects of the subject have been reviewed by many workers.…”
Section: Mode D' Action Des Insecticides Naturelsmentioning
confidence: 99%
“…The organophosphorus insecticides are a group of chemicals whose development is largely due to the pioneer work of the German chemist Gerhard Schrader which began in 1934. Geary (1953) gives a historical review of the work of Schrader. Since the publication of Schrader 1 s work (Schrader 1947 ;Martin and Shaw 1947), thousands of phosphorus compounds have been evaluated for use as insecticides.…”
Section: Organophosphorus Insecticidesmentioning
confidence: 99%